Two-dimensional chromatographic characterisation of PS-b-PEO copolymers at the critical conditions of their corresponding homopolymers - Grabowsky, Monika Elvira (Stellenbosch : Stellenbosch University, 2011)
Thesis (MSc)--Stellenbosch University, 2011.